Key Factors Affecting Sustainable Tourism in the Region of South Central Coast of Vietnam - Cong De NGUYEN; Thang Loi NGO; Ngoc My DO; Ngoc Tien NGUYEN (My University, 2020)
Key Factors Affecting Sustainable Tourism in the Region of South Central Coast of Vietnam
Keywords: Sustainable Tourism; South Central Coast; Key Factors